Ecologia, religião e ensino ecológico do magistério da Igreja Católica e da Igreja Evangélica Assembleia de Deus no Brasil (de 1990 a 2015). - Silva, Severino Arruda da (2018)
Developed as a master’s degree dissertation in Science of Religion, this bibliographic, qualitative and interdisciplinary research, investigated the relationship that Religions establish with the Ecology. Starts the perception that religious institutions do not promote the care with the environment in intensity and appropriate methodology, besides considering that the Religions have an essential paper in environmental awareness, because it stimulates the sensitivity of the human’s care being with the cosmos and with the mystery of our existence. Was accomplished research in academic texts published in the area of ecology and in the epistemological field of the Sciences of Religion, observing the period from 1990 to 2015. It was used as analysis parameter the interdisciplinary approach and the ecological paradigm advocated by Leonardo Boff. The dissertation was organized in three chapter: in the first, is presented the current ecological paradigm and its assumptions for the understanding of ecology in its main concepts. In the second, the Ecology in the main religious expressions of humanity with operating in Brazil. In the third chapter, it is made a critical study the ecological contributions of the magisterium of the Catholic Church and the Evangelical Church Assembly of God in Brazil. It is considered that both the Catholic Church as the Assemblies of God, does not promote an education that can help the faithful to seek to overcome the current socio-environmental challenges. However, the Vatican and the CNBB have addressed ecological themes in their documents, in brotherhood’s campaigns and pronouncements in forums and official visits. While in the Assemblies of God, the environmental issue is explained to Christians in the Sunday Biblical Schools, serving people of certain age groups, treating only the ethical questions related to the Christian stewardship, besides the escapist eschatological teaching, of this Church that is antagonistic to the care with the Planet. In view of this, it is necessary a change of theological and environmental position of this Church, in the sense of promoting environmental awareness and change of behavior of the community in defense of Nature.